Etiology of Foliar Blight of Indian Paintbrush (Castilleja tenuiflora) in Mexico - Solano-Báez, Alma Rosa; Trejo-Tapia, Gabriela; Kolařík, Miroslav; Ortiz-Álvarez, Jossue; Trejo-Espino, José Luis; Márquez-Licona, Guillermo (Microorganisms, 2024)
Castilleja tenuiflora is a native perennial plant used in traditional Mexican medicine. In June 2022, leaf blight symptoms were observed in a wild population of C. tenuiflora plants. Disease incidence was 80% and disease intensity reached up to 5% of the leaf area. Currently, there are no reports of pathogens causing leaf blight in this plant; therefore, this work aimed to identify the fungi responsible for the disease. The fungi recovered from the diseased tissue were characterized by means of pathogenicity tests and cultural, morphological, and molecular characterization. The information obtained revealed that Alternaria alternata and Alternaria gossypina are the pathogens responsible for the disease. This is the first report implicating species of Alternaria in causing leaf blight of C. tenuiflora in Mexico, as well as the first report of Alternaria gossypina also in Mexico. These pathogens may threaten the in situ conservation of native C. tenuiflora populations and limit their in vitro propagation. Future research lines should focus on determining the effect of these pathogens on metabolite production.
Keywords: Orobanchaceae; morphology; Alternaria; phylogeny; pathogenicity; Mexican medicinal plants